PELATIHAN PENULISAN KARYA TULIS ILMIAH BAGI MAHASISWA PRODI ADMINISTRASI PUBLIK - Rijal Rijal; Nasrullah Nasrullah; Abdul Latief Arda; Jusman Jusman; Hermawati Mappiwali; Abdul Rahman; Sitti Sahara Syamel (LPPM Universitas Bina Bangsa, 2024)
Changes in students' mindsets and lifestyles can influence a decrease in interest in writing scientific papers. With advances in technology and the popularity of social media, students tend to be more interested in things that are instant and consumer, thus ignoring the importance of self-development through activities such as writing scientific papers. Writing scientific papers is an important activity in building academic and professional capacity for students in the Public Administration study program. This writing training aims to develop analytical skills, improve communication skills, deepen understanding of public administration, encourage the development of creativity and innovation, and prepare students for careers in this field. By focusing on current and complex issues in public administration, this training provides students with the opportunity to explore and analyze relevant problems, as well as find innovative solutions. Through a structured approach and comprehensive guidance, students are encouraged to write clearly, persuasively and organizedly, so that they are able to convey policy analysis or recommendations accurately and effectively. Thus, training in writing scientific papers becomes a strong foundation for developing the intellectual and professional capacity of Public Administration students, as well as solid preparation to face future challenges in the work environment in the public sector